A sodium ion battery positive electrode, preparation method and application thereof

By growing Prussian blue analog on a metal foam substrate and coating reducing graphene oxide, the problem of poor conductivity of sodium ion batteries is solved, and the electrochemical performance and cycle life of the battery are improved.

CN118380542BActive Publication Date: 2025-03-25JIANGSU PYLON BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410827988.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-03-25
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

Sodium ion batteries have problems such as low energy density and poor conductivity, which affect their battery performance and cycle life.

Method used

Prussian blue analogue was grown on a metal foam substrate and coated with reduced graphene oxide thereon to construct a highly conductive hydrophobic cathode.

Benefits of technology

By building a highly conductive hydrophobic cathode, the capacity and electrochemical performance of the cathode material are improved, and the safety and cycle life of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a sodium ion battery positive electrode, a preparation method and application thereof, and relates to the technical field of sodium ion batteries. A highly conductive hydrophobic positive electrode can be constructed by growing a Prussian blue analog on a metal foam substrate and coating the Prussian blue analog with reduced graphene oxide. The positive electrode has an excellent three-dimensional structure, greatly improves the capacity of the positive electrode material, and is beneficial to improving the electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode, a preparation method thereof and applications thereof. Background Art

[0002] The positive active materials of sodium ion batteries mainly include layered oxide materials (such as nickel iron manganese oxide and copper iron manganese oxide), Prussian blue analog materials (such as iron-based Prussian white, etc.), polyanion materials (such as sodium iron sulfate, sodium iron phosphate, etc.), and the negative electrode is mainly carbon materials (such as hard carbon, soft carbon). The electrolyte of sodium ion batteries mainly uses esters and ethers as solvents. + It is prepared by metal salt (such as sodium fluoride salt, sodium borate salt, perchlorate, etc.) electrolyte and a variety of additives (such as film-forming, flame retardant, overcharge protection, etc.).

[0003] Although sodium-ion batteries have the advantages of good low-temperature performance, low cost, high safety and long cycle life, they still have serious problems such as low energy density and poor conductivity.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium ion battery positive electrode, a preparation method and application thereof, aiming to provide a high conductivity material and improve the safety and cycle life of the battery.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a sodium ion battery positive electrode, comprising a metal foam substrate, a Prussian blue analogue grown on the metal foam substrate, and reduced graphene oxide coated on the Prussian blue analogue;

[0008] The chemical formula of the Prussian blue analogue is A x M 1 [M 2 (CN) 6 ] y ·nH 2 O, M 1 and M 2 All represent transition metals connected via cyano groups, A represents a cation embedded in the framework space of the Prussian blue analog, and 0 <x<2,0<y<1。

[0009] In an optional embodiment, the mass ratio of the metal foam substrate, the Prussian blue analogue and the reduced graphene oxide is 100: (100-500): (10-50);

[0010] The metal foam substrate is selected from at least one of foamed copper, foamed iron, foamed nickel and foamed titanium.

[0011] In a second aspect, the present invention provides a method for preparing a positive electrode of a sodium ion battery according to any one of the aforementioned embodiments, comprising: growing a Prussian blue analogue on a metal foam substrate, and then coating the Prussian blue analogue with reduced graphene oxide.

[0012] In an optional embodiment, the process of growing a Prussian blue analog on a metal foam substrate comprises: mixing potassium ferrocyanide, sodium salt and a complexing agent to adjust the pH value to 3-4, and then hydrothermally reacting with the metal foam substrate, controlling the reaction temperature to 80° C.-100° C., and the reaction time to 5 h-8 h;

[0013] Preferably, the molar ratio of potassium ferrocyanide to sodium in the sodium salt is 1:(1-8);

[0014] Preferably, the sodium salt is selected from at least one of sodium chloride, sodium sulfate and sodium nitrate;

[0015] Preferably, the complexing agent is selected from at least one of sodium citrate, citric acid, ammonium bicarbonate and tartaric acid.

[0016] In an optional embodiment, the process of coating reduced graphene oxide on a Prussian blue analogue comprises: immersing a metal foam substrate on which a Prussian blue analogue is grown in a cationic surfactant solution so that the surface of the material carries a positive charge, then immersing the positively charged material in a graphene oxide dispersion to form a surface coating, and taking out the material and calcining it under an inert atmosphere;

[0017] Preferably, the cationic surfactant in the cationic surfactant solution is at least one selected from dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and benzalkonium chloride; more preferably, the immersion time in the cationic surfactant solution is 0.5h-2.0h.

[0018] In an optional embodiment, the positively charged material is immersed in the graphene oxide dispersion for 0.5 h to 2.0 h, and stirred during the infiltration process;

[0019] Preferably, the preparation process of the graphene oxide dispersion comprises: dispersing graphene oxide powder in water, ultrasonically treating for 0.5h-2.0h, and the mass concentration of the graphene oxide dispersion is 10-20%;

[0020] Preferably, the calcination temperature is 200° C.-300° C., and the calcination time is 1 h-3 h.

[0021] In an alternative embodiment, before growing the Prussian blue analog on the metal foam substrate, the metal foam substrate is pretreated to form an oxide layer on the surface.

[0022] In an optional embodiment, the pretreatment process includes: washing the metal foam substrate once to remove surface impurities, then treating it with an acid solution to remove the surface oxide layer, and then washing it twice; pre-oxidizing the foam substrate after the second washing in an oxygen-containing atmosphere, controlling the oxidation temperature to 100° C.-500° C., and the pre-oxidation time to 0.5 h-2 h;

[0023] Preferably, in the first washing, washing is performed sequentially with an organic solvent and water; in the second washing, washing is performed multiple times with water;

[0024] Preferably, the acid solution is a dilute hydrochloric acid aqueous solution with a concentration of 1 mol-2 mol.

[0025] In a third aspect, the present invention provides a sodium ion battery, comprising a sodium ion battery positive electrode according to any one of the aforementioned embodiments or a sodium ion battery positive electrode prepared by any one of the preparation methods according to the aforementioned embodiments.

[0026] In a fourth aspect, the present invention provides an electrical device comprising the sodium ion battery of the aforementioned embodiment.

[0027] The present invention has the following beneficial effects: by growing a Prussian blue analogue on a metal foam substrate and coating the Prussian blue analogue with reduced graphene oxide, a highly conductive hydrophobic positive electrode can be constructed, and the positive electrode has an excellent three-dimensional structure, which greatly improves the capacity of the positive electrode material and is beneficial to improving the electrochemical performance of the battery. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] An embodiment of the present invention provides a method for preparing a positive electrode of a sodium ion battery, comprising the following steps:

[0030] S1. Pretreatment of metal foam substrate

[0031] Before growing the Prussian blue analog on the metal foam substrate, the metal foam substrate is pretreated to form an oxide layer on the surface, thereby obtaining an oxide substrate with a dense and uniform surface, which is conducive to the subsequent uniform growth of the Prussian blue analog.

[0032] In some embodiments, the metal foam substrate is selected from at least one of foam copper, foam iron, foam nickel and foam titanium. The above metal foam substrates are all suitable for the preparation method provided in the embodiments of the present invention, and can prepare a positive electrode with higher capacity.

[0033] In some embodiments, the pretreatment process includes: washing the metal foam substrate once to remove surface impurities, then treating it with acid to remove the surface oxide layer, and then washing it a second time; pre-oxidizing the foam substrate after the second washing in an oxygen-containing atmosphere to evenly oxidize the surface.

[0034] Furthermore, during one washing, washing is performed sequentially with an organic solvent and water to fully remove surface impurities. Specifically, the type of the organic solvent is not limited, and may be acetone, but is not limited thereto.

[0035] Furthermore, the acid solution can be a dilute hydrochloric acid aqueous solution with a concentration of 1 mol-2 mol, which can quickly remove the original uneven oxide layer on the surface of the metal foam substrate. Specifically, the concentration of the dilute hydrochloric acid aqueous solution can be 1.0 mol, 1.5 mol, 2.0 mol, etc.

[0036] Furthermore, during the secondary washing, water is used for multiple washings to remove the acid on the surface. The number of washings is not limited, such as 3 times or more.

[0037] Furthermore, the pre-oxidation process can be carried out in a tube furnace, the oxidation temperature is controlled to be 100°C-500°C, the pre-oxidation time is 0.5h-2h, and a uniform oxide layer is formed by adjusting the pre-oxidation temperature and time. Specifically, the oxidation temperature can be 100°C, 200°C, 300°C, 400°C, 500°C, etc., and the pre-oxidation time can be 0.5h, 1.0h, 1.5h, 2.0h, etc.

[0038] Specifically, the pre-oxidation atmosphere can be a pure oxygen atmosphere, and the surface of the foam substrate is heated in pure oxygen. 2 The surface of the alloy was evenly oxidized under the environment, and a dense and uniform oxidized base was formed on the surface.

[0039] S2. In situ growth of Prussian blue analogs

[0040] Growing Prussian blue analogs on metal foam substrates is conducive to the construction of three-dimensional conductive structures with ultra-high specific surface area.

[0041] In some embodiments, the process of growing a Prussian blue analog on a metal foam substrate includes: mixing potassium ferrocyanide, sodium salt and a complexing agent to adjust the pH value to 3-4, and then performing a hydrothermal reaction with the metal foam substrate, controlling the reaction temperature to 80°C-100°C, and the reaction time to 5h-8h. Under the action of the complexing agent, potassium ferrocyanide and sodium salt react to form a Prussian blue analog. The temperature and time of the hydrothermal reaction are preferably within the above range, which can make the morphology of the grown Prussian blue analog more uniform.

[0042] Specifically, the pH value of the reaction can be adjusted with dilute hydrochloric acid, and the adjusted pH value can be 3.0, 3.3, 3.5, 3.8, 4.0, etc. The temperature of the hydrothermal reaction can be 80°C, 85°C, 90°C, 95°C, 100°C, etc., and the reaction time can be 5h, 6h, 7h, 8h, etc.

[0043] In some embodiments, the molar ratio of potassium ferrocyanide to sodium in the sodium salt is 1:(1-8), such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, etc. By adjusting the molar ratio of potassium ferrocyanide to sodium salt, K + The ratio of embedded Prussian blue analogs, K + Relative Na + It has lower hydration energy and weaker ability to carry crystal water. The molar ratio of potassium ferrocyanide and sodium salt is preferably within the above range, which can further reduce the content of crystal water in the product. The chemical formula of Prussian blue analogue is A x M 1 [M 2 (CN) 6 ] y ·nH 2 O, M 1 and M 2 All represent transition metals connected via cyano groups, A represents a cation embedded in the framework space of the Prussian blue analog, and 0 <x<2,0<y<1。

[0044] Furthermore, the sodium salt is selected from at least one of sodium chloride, sodium sulfate and sodium nitrate, and the sodium salt can be any one or more of the above; the complexing agent is selected from at least one of sodium citrate, citric acid, ammonium bicarbonate and tartaric acid, and the complexing agent can be any one or more of the above.

[0045] S3, coated reduced graphene oxide

[0046] Reduced graphene oxide is coated on a Prussian blue analogue to improve the conductivity of the product. The prepared positive electrode has an excellent three-dimensional structure, high conductivity, hydrophobic properties and low crystalline water content, which greatly improves the capacity of the positive electrode material and stimulates the potential of Prussian blue material for sodium-ion batteries.

[0047] In some embodiments, the process of coating reduced graphene oxide on a Prussian blue analog includes: soaking a metal foam substrate on which a Prussian blue analog is grown in a cationic surfactant solution so that the surface of the material carries a positive charge, then soaking the positively charged material in a graphene oxide dispersion to form a surface coating, and then taking out the material and calcining it under an inert atmosphere. By subjecting the surface of the material to positive charge treatment, the uniformity of the graphene oxide coating can be improved because the graphene oxide is negatively charged. Calcination under an inert atmosphere not only improves the crystallinity of the composite material and reduces the crystal water content, but also reduces the graphene oxide and obtains hydrophobic reduced graphene oxide.

[0048] In some embodiments, the cationic surfactant in the cationic surfactant solution is selected from at least one of dodecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride and benzalkonium chloride, and the cationic surfactant can be any one or more of the above, and the cationic surfactant and water can be mixed to form a cationic surfactant aqueous solution for soaking the material. The soaking time in the cationic surfactant solution is 0.5h-2.0h, such as 0.5h, 1.0h, 1.5h, 2.0h, etc.

[0049] In some embodiments, the preparation process of the graphene oxide dispersion includes: dispersing graphene oxide powder in water, and ultrasonically treating for 0.5h-2.0h (such as 0.5h, 1.0h, 1.5h, 2.0h) to improve the uniformity of graphene oxide dispersion. The mass concentration of the graphene oxide dispersion is 10-20% (such as 10%, 13%, 15%, 18%, 20%, etc.) to make the coating amount of graphene oxide more appropriate.

[0050] Furthermore, the positively charged material is immersed in the graphene oxide dispersion for 0.5 h to 2.0 h, and stirred during the immersion process to improve the uniformity of the coating. Specifically, the immersion time can be 0.5 h, 1.0 h, 1.5 h, 2.0 h, etc.

[0051] In some embodiments, the calcination temperature is 200°C-300°C, the calcination time is 1h-3h, and the calcination atmosphere can be argon, nitrogen, etc. The calcination temperature and time are preferably within the above range to reduce the graphene oxide more fully and reduce the crystal water content in the product. Specifically, the calcination temperature can be 200°C, 250°C, 300°C, etc., and the calcination time can be 1h, 2h, 3h, etc.

[0052] The embodiment of the present invention provides a sodium ion battery positive electrode, comprising a metal foam substrate, a Prussian blue analogue grown on the metal foam substrate, and reduced graphene oxide coated on the Prussian blue analogue. The sodium ion battery positive electrode provided by the embodiment of the present invention is a highly conductive hydrophobic positive electrode with an excellent three-dimensional structure, which can greatly improve the capacity of the positive electrode material and is conducive to improving the electrochemical performance of the battery.

[0053] In some embodiments, the mass ratio of the metal foam substrate, the Prussian blue analogue and the reduced graphene oxide is 100:(100-500):(10-50), such as 100:100:10, 100:200:20, 100:300:30, 100:400:40, 100:500:50, etc., and the electrochemical performance of the positive electrode can be further improved by adjusting the mass ratio of the metal foam substrate, the Prussian blue analogue and the reduced graphene oxide.

[0054] An embodiment of the present invention provides a sodium ion battery, including the above-mentioned sodium ion battery positive electrode, and may also include a negative electrode plate, an electrolyte, a separator, etc., to form a complete battery structure.

[0055] An embodiment of the present invention provides an electrical device, including the sodium ion battery mentioned above, and the sodium ion battery is used for power supply. The specific type of the electrical device is not limited, such as a mobile device, an electric vehicle, etc.

[0056] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0057] Example 1

[0058] This embodiment provides a method for preparing a positive electrode of a sodium ion battery, comprising the following steps:

[0059] (1) Purchase a commercial nickel foam substrate (purchased from Keliyuan Company, the model is a continuous strip nickel foam, the length, width and height are 10 cm × 10 cm × 1 cm, the same below), remove surface impurities from the foam substrate with acetone and pure water, soak the foam substrate in a 1M dilute hydrochloric acid aqueous solution for 10 min to remove the original uneven oxide layer on the surface of the foam substrate, and then wash it with pure water three times.

[0060] (2) Place the foam substrate treated in step (1) into a tubular furnace and introduce pure O 2 , temperature 100℃, pre-oxidation 1h.

[0061] (3) Weigh 1 mol potassium ferrocyanide, 4 mol sodium chloride and 0.2 mol sodium citrate, adjust the pH value to 3-4 with 2 M dilute hydrochloric acid, stir evenly, and place in a hydrothermal reactor.

[0062] (4) The foam substrate treated in step (2) is placed in the hydrothermal reactor of step (3), and then placed in a 90° C. oven for reaction for 6 h to obtain a foam substrate@Prussian blue analog positive electrode.

[0063] (5) Weigh a cationic surfactant (dodecyltrimethylammonium chloride) and mix with water to prepare a 2M cationic surfactant aqueous solution. Soak the foam substrate@Prussian blue analog positive electrode obtained in step (4) in the cationic surfactant aqueous solution for 1 h to obtain a positively charged foam substrate@Prussian blue analog.

[0064] (6) Weigh flaky graphene oxide powder (single layer, Xianfeng Nano, XF002-3, the same below) and disperse it in an aqueous solution. Ultrasonicate for 1 h to obtain a graphene oxide dispersion with a concentration of 20% wt. The dispersion is sealed in a beaker and set aside.

[0065] (7) The positively charged foam substrate @ Prussian blue analogue in step (5) is suspended at the mouth of the beaker in step (6), and the positive electrode is immersed in the middle of the solution. The agitator is stirred for 1 hour, and the surface of the Prussian blue analogue is uniformly coated with graphene oxide to obtain a foam substrate @ Prussian blue analogue @ graphene oxide positive electrode.

[0066] (8) The positive electrode of foam substrate @ Prussian blue analog @ graphene oxide was placed in a tubular furnace, introduced with argon gas, and calcined at 250 °C for 2 h to obtain foam substrate @ Prussian blue analog @ reduced graphene oxide.

[0067] The electrochemical performance of the positive electrode material prepared in Test Example 1 was tested using the following test method:

[0068] The positive electrode uses a Prussian blue analogue nickel foam positive electrode;

[0069] The negative electrode is prepared by coating a hard carbon water system formula on a carbon-coated aluminum foil. The hard carbon water system formula is as follows: water is used as the solvent, the solid substance consists of hard carbon, SP, SBR (styrene-butadiene rubber) and CMC (sodium carboxymethyl cellulose), the mass ratio of hard carbon, SP, SBR and CMC is 90:3:5:2, and the mass ratio of solid substance to water is 1:1.

[0070] The diaphragm is made of polypropylene;

[0071] The electrolyte is 1M sodium salt (NaPF 6 ) + ester solvent (ethylene carbonate EC and diethyl carbonate DMC, the volume ratio of EC and DMC is 4:6) + 1% by mass of vinylene carbonate;

[0072] A laminated 5Ah soft-pack battery was prepared.

[0073] The test results of the positive electrode material prepared in Example 1 are as follows: 0.1C / 0.1C charge / discharge capacity (90.5mAh / g), first coulombic efficiency (83.5%), capacity retention rate at 5C rate (92.5%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (98.91%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (4mL), 300 cycles of 0.5C / 1C high temperature (45°C, the same below), and capacity retention rate of 90.6%.

[0074] Example 2

[0075] This embodiment provides a method for preparing a positive electrode of a sodium ion battery, comprising the following steps:

[0076] (1) Purchase a commercial nickel foam substrate, remove surface impurities from the foam substrate with acetone and pure water, soak the foam substrate in a 2M dilute hydrochloric acid aqueous solution for 5 minutes to remove the original uneven oxide layer on the surface of the foam substrate, and then wash it with pure water three times.

[0077] (2) Place the foam substrate treated in step (1) into a tubular furnace and introduce pure O 2 , temperature 500℃, pre-oxidation 0.5h.

[0078] (3) Weigh 1 mol potassium ferrocyanide, 2 mol sodium chloride and 0.15 mol sodium citrate, adjust the pH value to 3-4 with 1.5 M dilute hydrochloric acid, stir evenly, and place in a hydrothermal reactor.

[0079] (4) The foam substrate treated in step (2) is placed in the hydrothermal reactor of step (3), and then placed in an oven at 80° C. for reaction for 8 h to obtain a foam substrate@Prussian blue analog positive electrode.

[0080] (5) Weigh a cationic surfactant (dodecyltrimethylammonium chloride) and mix with water to prepare a 1 M cationic surfactant aqueous solution. Soak the foam substrate @ Prussian blue analog positive electrode obtained in step (4) in the cationic surfactant aqueous solution for 0.5 h to obtain a positively charged foam substrate @ Prussian blue analog.

[0081] (6) Weigh flaky graphene oxide powder (multilayer, Xianfeng Nano, XF002-2, the same below) and disperse it in an aqueous solution. Ultrasonicate for 0.5 h to obtain a graphene oxide dispersion with a concentration of 10% wt. The dispersion was sealed in a beaker for later use.

[0082] (7) The positively charged foam substrate @ Prussian blue analogue in step (5) is suspended at the mouth of the beaker in step (6), and the positive electrode is immersed in the middle of the solution. The agitator is stirred for 1 hour, and the surface of the Prussian blue analogue is uniformly coated with graphene oxide to obtain a foam substrate @ Prussian blue analogue @ graphene oxide positive electrode.

[0083] (8) The positive electrode of foam substrate @ Prussian blue analog @ graphene oxide was placed in a tube furnace, introduced with argon gas, and calcined at 200 °C for 3 h to obtain foam substrate @ Prussian blue analog @ reduced graphene oxide.

[0084] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0085] The test results of the positive electrode material prepared in Example 2 are as follows: 0.1C / 0.1C charge / discharge capacity (85.6mAh / g), first coulombic efficiency (80.4%), capacity retention rate at 5C rate (90.4%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (99.55%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (3mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 92.7%.

[0086] Example 3

[0087] This embodiment provides a method for preparing a positive electrode of a sodium ion battery, comprising the following steps:

[0088] (1) Purchase a commercial nickel foam substrate, remove surface impurities from the foam substrate with acetone and pure water, soak the foam substrate in a 1.5M dilute hydrochloric acid aqueous solution for 7 minutes to remove the original uneven oxide layer on the surface of the foam substrate, and then wash it with pure water three times.

[0089] (2) Place the foam substrate treated in step (1) into a tubular furnace and introduce pure O 2 , temperature 100℃, pre-oxidation 2h.

[0090] (3) Weigh 1 mol of potassium ferrocyanide, 6 mol of sodium chloride and 0.1 mol of sodium citrate, adjust the pH value to 3-4 with 1 M dilute hydrochloric acid, stir evenly, and place in a hydrothermal reactor.

[0091] (4) The foam substrate treated in step (2) is placed in the hydrothermal reactor of step (3), and then placed in an oven at 100° C. for reaction for 5 hours to obtain a foam substrate@Prussian blue analog positive electrode.

[0092] (5) Weigh a cationic surfactant (dodecyltrimethylammonium chloride) and mix with water to prepare a 2M cationic surfactant aqueous solution. Soak the foam substrate@Prussian blue analog positive electrode obtained in step (4) in the cationic surfactant aqueous solution for 2.0 h to obtain a positively charged foam substrate@Prussian blue analog.

[0093] (6) Weigh flaky graphene oxide powder (single layer) and disperse it in an aqueous solution. Ultrasonicate for 2.0 h to obtain a graphene oxide dispersion with a concentration of 20% wt. The dispersion is sealed in a beaker and set aside.

[0094] (7) The positively charged foam substrate @ Prussian blue analogue in step (5) is suspended at the mouth of the beaker in step (6), and the positive electrode is immersed in the middle of the solution. The agitator is stirred for 1 hour, and the surface of the Prussian blue analogue is uniformly coated with graphene oxide to obtain a foam substrate @ Prussian blue analogue @ graphene oxide positive electrode.

[0095] (8) The positive electrode of foam substrate @ Prussian blue analog @ graphene oxide was placed in a tube furnace, introduced with argon gas, and calcined at 300 °C for 1 h to obtain foam substrate @ Prussian blue analog @ reduced graphene oxide.

[0096] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0097] The test results of the positive electrode material prepared in Example 3 are as follows: 0.1C / 0.1C charge / discharge capacity (95.2mAh / g), first coulombic efficiency (86.2%), capacity retention rate at 5C rate (94.3%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (98.12%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (5mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 87.1%.

[0098] Example 4

[0099] The only difference from Example 1 is that the foamed nickel substrate is replaced by a foamed iron substrate of the same size.

[0100] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0101] The test results of the positive electrode material prepared in Example 4 are as follows: 0.1C / 0.1C charge / discharge capacity (120.6mAh / g), first coulombic efficiency (93.2%), capacity retention rate at 5C rate (95.7%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (95.85%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (10mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 80.8%.

[0102] Example 5

[0103] The only difference from Example 1 is that the foamed nickel substrate is replaced by a foamed copper substrate of the same size.

[0104] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0105] The test results of the positive electrode material prepared in Example 5 are as follows: 0.1C / 0.1C charge / discharge capacity (98.6mAh / g), first coulombic efficiency (88.7%), capacity retention rate at 5C rate (97.1%), 0.1C / 0.1C charge / discharge cycle 100 cycles capacity retention rate (97.63%), 0.1C / 0.1C charge / discharge cycle 100 cycles gas production (6mL). 0.5C / 1C high temperature cycle 300 cycles, capacity retention rate 83.6%.

[0106] Example 6

[0107] The only difference from Example 1 is that the nickel foam substrate is replaced by a titanium foam substrate of the same size.

[0108] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0109] The test results of the positive electrode material prepared in Example 6 are as follows: 0.1C / 0.1C charge / discharge capacity (98.93mAh / g), first coulombic efficiency (87.9%), capacity retention rate at 5C rate (98.8%), 0.1C / 0.1C charge / discharge cycle 100 cycles capacity retention rate (99.21%), 0.1C / 0.1C charge / discharge cycle 100 cycles gas production (6mL). 0.5C / 1C high temperature cycle 300 cycles, capacity retention rate 88.6%.

[0110] Example 7

[0111] The only difference from Example 1 is that the amount of raw materials used in step (3) is different, 1 mol potassium ferrocyanide and 8 mol sodium chloride. (Compared with Example 1, the amount of sodium chloride is increased, and sodium citrate is not added)

[0112] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0113] The test results of the positive electrode material prepared in Example 7 are as follows: 0.1C / 0.1C charge / discharge capacity (99.63mAh / g), first coulombic efficiency (89.7%), capacity retention rate at 5C rate (95.8%), 0.1C / 0.1C charge / discharge cycle 100 cycles capacity retention rate (97.73%), 0.1C / 0.1C charge / discharge cycle 100 cycles gas production (9mL). 0.5C / 1C high temperature cycle 300 cycles, capacity retention rate 76.2%.

[0114] Example 8

[0115] The only difference from Example 1 is that the reaction temperature in step (4) is 150°C.

[0116] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0117] The test results of the positive electrode material prepared in Example 8 are as follows: 0.1C / 0.1C charge / discharge capacity (80.5mAh / g), first coulombic efficiency (75.5%), capacity retention rate at 5C rate (88.5%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (90.91%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (4mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 76.6%.

[0118] Example 9

[0119] The only difference from Example 1 is that the reaction temperature of step (4) is 200°C.

[0120] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0121] The test results of the positive electrode material prepared in Example 9 are as follows: 0.1C / 0.1C charge / discharge capacity (70.5mAh / g), first coulombic efficiency (68.5%), capacity retention rate at 5C rate (80.5%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (80.91%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (3mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 70.6%.

[0122] Comparative Example 1

[0123] The only difference from Example 1 is that step (1) and step (2) are not performed.

[0124] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0125] The test results of the positive electrode material prepared in Comparative Example 1 are as follows: Without three-dimensional substrate impurity removal and pre-oxidation, the main problem is that the growth of active substances is less and the purity is low. 0.1C / 0.1C charge / discharge capacity (65.5mAh / g), first coulomb efficiency (65.7%), capacity retention rate at 5C rate (74.7%), 0.1C / 0.1C charge / discharge cycle 100 cycles capacity retention rate (73.57%), 0.1C / 0.1C charge / discharge cycle 100 cycles gas production (20mL), 0.5C / 1C high temperature cycle 300 cycles, capacity retention rate 64.8%.

[0126] Comparative Example 2

[0127] The only difference from Example 1 is that steps (5) to (7) are not performed.

[0128] The method for preparing 5Ah soft-pack batteries is based on Example 1.

[0129] The test results of the positive electrode material prepared in Comparative Example 2 are as follows: 0.1C / 0.1C charge / discharge capacity (81.4mAh / g), first coulombic efficiency (76.3%), capacity retention rate at 5C rate (92.5%), capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge cycles (86.88%), gas production after 100 cycles of 0.1C / 0.1C charge / discharge cycles (13mL), 300 cycles of 0.5C / 1C high temperature cycles, and a capacity retention rate of 75.6%.

[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode for a sodium ion battery, characterized in that: The positive electrode of the sodium ion battery comprises a metal foam substrate, a Prussian blue analogue is grown on the metal foam substrate, and the Prussian blue analogue is coated with reduced graphene oxide; The chemical formula of the Prussian blue analogue is A x M1[M2(CN)6] y nH2O, M1 and M2 both represent transition metals connected via cyano groups, A represents a cation embedded in the framework space of the Prussian blue analog, 0 <x<2,0<y<1; The metal foam substrate is nickel foam; The method for preparing the positive electrode of the sodium ion battery comprises: pre-treating the metal foam substrate to form an oxide layer on the surface; growing the Prussian blue analog on the metal foam substrate having the oxide layer, and then coating the Prussian blue analog with reduced graphene oxide; The pretreatment process includes: washing the metal foam substrate once to remove surface impurities, then treating it with acid to remove the surface oxide layer, and then washing it twice; pre-oxidizing the foam substrate after the second washing in an oxygen-containing atmosphere, controlling the oxidation temperature to 100° C.-500° C., and the pre-oxidation time to 0.5 h-2 h; The process of growing the Prussian blue analogue comprises: mixing potassium ferrocyanide, sodium salt and a complexing agent to adjust the pH value to 3-4, and then hydrothermally reacting with the metal foam substrate, controlling the reaction temperature to 80°C-100°C, and the reaction time to 5h-8h; the complexing agent is selected from at least one of sodium citrate, citric acid, ammonium bicarbonate and tartaric acid; The process of coating reduced graphene oxide on the Prussian blue analogue comprises: immersing the metal foam substrate on which the Prussian blue analogue is grown in a cationic surfactant solution to make the surface of the material carry positive charge, then immersing the positively charged material in a graphene oxide dispersion to form a surface coating, and taking out the material and calcining it under an inert atmosphere.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the metal foam substrate, the Prussian blue analogue and the reduced graphene oxide is 100:(100-500):(10-50).

3. The preparation method according to claim 1, characterized in that: The molar ratio of potassium ferrocyanide to sodium in the sodium salt is 1:(1-8); The sodium salt is selected from at least one of sodium chloride, sodium sulfate and sodium nitrate.

4. The preparation method according to claim 1, characterized in that: The cationic surfactant in the cationic surfactant solution is selected from at least one of dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and benzalkonium chloride; and the immersion time in the cationic surfactant solution is 0.5h-2.0h.

5. The preparation method according to claim 4, characterized in that: Immersing the positively charged material in the graphene oxide dispersion for 0.5 h to 2.0 h, stirring during the immersion process; The preparation process of the graphene oxide dispersion comprises: dispersing graphene oxide powder in water, ultrasonically treating for 0.5h-2.0h, wherein the mass concentration of the graphene oxide dispersion is 10-20%; The calcination temperature is 200°C-300°C, and the calcination time is 1h-3h.

6. The preparation method according to claim 1, characterized in that: In the first washing, the organic solvent and water are used for washing in sequence; in the second washing, water is used for washing multiple times; The acid solution is a dilute hydrochloric acid aqueous solution with a concentration of 1 mol-2 mol.

Citation Information

Patent Citations

  • Graphene rapidly-coated Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN108565422A

  • Preparation method and application of self-supporting substrate loaded Prussian blue composite material

    CN116040614A